Differential regulation of proliferation and neuronal differentiation in adult rat spinal cord neural stem/progenitors by ERK1/2, Akt, and PLCγ - Chan, Wai Si; Sideris, Alexandra; Sutachan, Jhon J.; Montoya G., Jose V.; Blanck, Thomas J.; Recio-Pinto, Esperanza (Frontiers in Molecular Neuroscience, 2013)
Proliferation of endogenous neural stem/progenitor cells (NSPCs) has been identified in both normal and injured adult mammalian spinal cord. Yet the signaling mechanisms underlying the regulation of adult spinal cord NSPCs proliferation and commitment toward a neuronal lineage remain undefined. In this study, the role of three growth factor-mediated signaling pathways in proliferation and neuronal differentiation was examined. Adult spinal cord NSPCs were enriched in the presence of fibroblast growth factor 2 (FGF2). We observed an increase in the number of cells expressing the microtubule-associated protein 2 (MAP2) over time, indicating neuronal differentiation in the culture. Inhibition of the mitogen-activated protein kinase or extracellular signal-regulated kinase (ERK) kinase 1 and 2/ERK 1 and 2 (MEK/ERK1/2) or the phosphoinositide 3-kinase (PI3K)/Akt pathways suppressed active proliferation in adult spinal cord NSPC cultures; whereas neuronal differentiation was negatively affected only when the ERK1/2 pathway was inhibited. Inhibition of the phospholipase C gamma (PLCy) pathway did not affect proliferation or neuronal differentiation. Finally, we demonstrated that the blockade of either the ERK1/2 or PLCy signaling pathways reduced neurite branching of MAP2+ cells derived from the NSPC cultures. Many of the MAP2+ cells expressed synaptophysin and had a glutamatergic phenotype, indicating that over time adult spinal cord NSPCs had differentiated into mostly glutamatergic neurons. Our work provides new information regarding the contribution of these pathways to the proliferation and neuronal differentiation of NSPCs derived from adult spinal cord cultures, and emphasizes that the contribution of these pathways is dependent on the origin of the NSPCs.